Testing a Path Model of Organizational Justice and Correctional Staff Job Stress Among Southern Correctional Staff. (October 2019) - Lambert, Eric G.; Keena, Linda D.; Haynes, Stacy H.; May, David; Ricciardelli, Rosemary; Leone, Matthew
Job stress has many negative effects on correctional staff. We proposed and tested a path model of transactional, procedural, and distributive justice's direct and indirect effects on the job stress of 322 surveyed correctional staff, including 219 correctional officers, at a maximum security Southern prison. Findings indicated that procedural, distributive, and transactional justice affected job stress. Specifically, the proposed path model was supported, such that procedural justice had an indirect effect on job stress through distributive justice, and transactional and distributive justice had direct, negative effects on job stress. Transactional justice also had indirect effects on job stress through procedural and distributive justice. Taken together, the results suggest that organizational justice plays an important role in reducing correctional staff job stress.